CATCHABILITY DIFFERENCE OF GILL NET AND COLLAPSIBLE BAITED POT FOR JAPANESE ROCK CRAB - Dahri lskandar; Yoshiyuki Suzuki; Daisuke Shiode; Fuxiang Hu; Tadashi Tokai (Research Center for Fisheries, 2006)
The objective of this experiment is to know the catchabjlity of gill net and collapsible baited pot on Japanese rock crab. Result shows that gillnet caught more than twenty species other than Japanese rock crab.